Ecological Benefits of Five Years Old Social Forestry Village Woodlots in Orissa - Patnaik, L. K.; Bharthuar, A. (Indian Forester, 1991)
The village woodlots raIsed in the SIOA assisted SocIal Forestry Project activities in Orissa though small in size, isolated and scattered have had a positive effect on the environment in terms of (I) cooler atmosphere, (II) more permeable-greater moisture retaining nutrients of sub-soil levels. (III) greater fuel availability and use. It has also led to an Increasing awareness about benefits of tree planting and have helped to evolve methods to control grazing through collective community management.